KADAR LOGAM BERAT Pb PADA IKAN BERONANG (Siganus sp), LAMUN, SEDIMEN DAN AIR DI WILAYAH PESISIR KOTA BONTANG-KALIMANTAN TIMUR - Muhammad Zainuri; S Sudrajat; Evi Sulistiani Siboro (Jurnal Kelautan, 2011)
Study biomagnifition of lead (Pb) of sea water, Seagrass, “baronang” species of fish and sediment, on Bontang coastal waters. The objective of this research was to know the compound Pb in sea water, sediment, seagress and “baronang”. And to know the adsorption and bioconcentration of them. This research conducted through field survey and laboratorium analysis, where the result elaborated as quantitative descriptive since Mei to October 2009, covering had taken the samples, sample preparation, laboratorium analysis, tabulation and data analysis. The samples analyzed by purposive method to provide accurate and efficient data in order to achive the research objective. The result showed that, the heavy metal of Pb in the sea water from 0,796 to 0,997 ppm, in sediment from 2,862 to 3,970 ppm, in seagrass from 0,114 to 0,567 ppm), and in baronang from 0,044 to 0,229ppm (samples of liver of fish) and from 0,269 to 0,574 ppm (samples of muscle). By this result had be known that, the Pb content in sediment is higher than in both seagrass and baronang. By the partial statistical analysis result shows that the Pb content in all of samples (water, seagrass,sediment and baronang fishes) differed, significantly. The adsorption and bioconsentration factors analysis toward Pb shows that in sediment were from 3,312 to 3,982 ppm, seagrass were from 0,116 to 0,712 ppm, and baronang”’ muscle from 0,272 to 0,721 ppm, also in liver from 0,044 to 0,287 ppm. Keywords: Pb, Heavy Metals, Seagrass, Baronang